Does intra‐operative verapamil administration in kidney transplantation improve graft function. Issue 8 (1st July 2019) - Gupta, Nidhi; Caldas, Mauricio; Sharma, Nitin; Bidnur, Samir; Ghosh, Sunita; Todd, Gerald T.; Moore, Ronald B.
Abstract: The role of the calcium channel blocker (verapamil) in kidney transplant is controversial. Verapamil has been hypothesized to mitigate ischemia reperfusion injury (IRI) to the allograft. Herein, we evaluated the effect of intra‐operative verapamil administration in a large cohort of kidney transplants. Total 684 transplants were performed during 2007‐2017. Of these, 348 (50.9%) transplants received verapamil (2.5 mg) Ver (+), and 336 (49.1%) did not, Ver (−). Based on the donor type, the study was divided into three groups; living donor (LD) (N = 270), neurological determination of death (NDD) (N = 394), and donation after cardiac death (DCD) (N = 20). Ver (−) subgroup had more diabetic recipients as compared to Ver (+) subgroup in LD and NDD groups ( P < 0.05). No significant difference was found for delayed graft function in any of the group ( P > 0.05). Cold ischemia time and dialysis requirement were significantly higher in Ver (+) LD and NDD groups, respectively. Except for DCD group, there was no significant difference in eGFR (mL/min) immediately and 6 months after kidney transplant in any of the groups. Furthermore, univariate and multivariate logistic regression analysis was performed to account for potential confounders, but verapamil administration did not improve graft function in any of the groups ( P > 0.05) after transplant.